Sistem Informasi Bimbingan Skripsi Berbasis Web Di Universitas Stella Maris Sumba - Frederikus Deritno Malo; Elfira Umar; Paulus Mikku Ate (Journal Of Informatics And Busisnes, 2024)
Every student in the information systems study program at Stella Maris University, Sumba can start writing a thesis if they have fulfilled the terms and conditions for writing a thesis. In completing the thesis, students will be accompanied by a supervisor. The supervisor has academic responsibility for the thesis produced by the students they supervise, in terms of scientific correctness and writing techniques during the implementation of the guidance process. The thesis guidance process cannot run smoothly and on time when lecturers and students have their own busy schedules which causes there to be no suitable time to meet. This obstacle can make existing problems in writing a thesis unable to be solved immediately. Apart from that, lecturers also find it difficult to monitor the students they supervise because the number of students they supervise is not small. To avoid this, in this research a web-based thesis guidance information system was designed and built at Stella Maris University, Sumba. Results of designing and building a web-based thesis guidance information system. This web- based information system consists of three users, namely administrators or study programs, lecturers and students, where each user has different access.